Prognostic value of red blood cell distribution width-standard deviation (RDW-SD) in patients operated on due to non-small cell lung cancer - Łochowski, Mariusz (J Thorac Dis, 2020)
BACKGROUND: The aim of the study was to determine a survival prognostic value of selected blood morphological rates of patients, operated on due to non-small cell lung cancer (NSCLC). METHODS: The study was conducted on 532 patients, surgically treated due to NSCLC, in stages IA–IIIA, 174 females and 358 males, mean age 63.6 years (36–84 years) were included in the study. Blood parameters and clinical factors were included in statistical analysis, in order to determine potential prognostic values of red blood cell distribution width-standard deviation (RDW-SD), mean corpuscular volume (MCV) of red cell and hemoglobin. Factors contained: age, sex, smoking history, histopathological diagnosis, T category, N category, age-adjusted Charlson Comorbidity Index (CCI), number of lymphocytes, neutrophils, monocytes, platelets, the neutrophil to lymphocyte ratio (NLR) and the platelet to lymphocyte ratio (PLR), kind of surgery, patient survival. RESULTS: The univariate analysis revealed a dependence of the value of RDW-SD and CCI values, the number of monocytes, NLR and PLR values, neoplasia stage and the overall survival. The multivariate analysis confirmed that not only N2 category and the value of CCI above 4 are negative prognostication factors, but also RDW-SD above 43 fL (P=0.00007) and PLR above 138 (P=0.001) are such negative factors of survival prognosis. CONCLUSIONS: RDW-SD is an independent and significant prognostic factor of patients’ survival operated on due to NSCLC.